INCREASING MATHEMATICS LEARNING OUTCOMES THROUGH CONCRETE LEARNING MEDIA ON CONSTRUCTION NETWORKS IN CLASS V STUDENTS ROOM - Ajeng Permata Masfiana; Agung Setyawan (Citra Dharma Cindekia, 2022)
This study aims to improve student learning outcomes of mathematics content through concrete learning media on the material of building nets for class V MI Bani Hasyim Lengkong Cerme Gresik. This type of research is Classroom Action Research using a research design from Kemmis and Tagart which consists of two cycles with each cycle consisting of one meeting. The subjects of this study were students of class V MI Bani Hasyim Lengkong Cerme Gresik, totaling 14 students consisting of 4 male students and 10 female students. Data collection techniques used are structured interviews, tests (pre-test and post-test), and documentation. The data analysis technique used is qualitative. The results of the Classroom Action Research showed that there was an increase in the actions of cycle I and cycle II. The learning outcomes of fifth graders experienced an increase in the content of mathematics after using concrete learning media. This is indicated by an increase in the percentage of complete learning outcomes and the average learning outcomes of the fifth grade students of MI Bani Hasyim.